Case Report: Three-dimensional characteristics of craniofacial morphology in facial asymmetry due to unilateral coronal synostosis - Fukunaga, Tomohiro; Shigemi, Shohei; Konno, Masahiro; Uechi, Jun; Yoshizawa, Mitsuhiro; Kishikawa, Akiko; Imai, Yoshimichi; Kitaura, Hideki; Mizoguchi, Itaru (Frontiers in Dental Medicine, 2025)
This case report describes the three-dimensional (3D) craniofacial morphology of a patient with severe facial asymmetry caused by unilateral coronal synostosis. The patient was an 11-year-and-3-month-old girl at the time of the first examination. Facial photographs revealed upper facial deviation toward the right (affected) side and lower facial deviation toward the left (non-affected) side. The nasal bridge was bent toward the non-affected side, and the external canthus on the affected side was retracted superolaterally. The midline of the lower dentition deviated toward the non-affected side. Molar relationships were Class III on the affected side and Class I on the non-affected side. A virtual fusion model of the skull and dentition was reconstructed and analyzed using a 3D coordinate system. The model demonstrated absence of the right coronal and sphenofrontal sutures, deviation of the nasal pyramid and vomer toward the affected side, and anterior displacement of the petrous bone. Unlike typical facial symmetry cases, this case exhibited a prominently anterior glenoid fossa and reduced mandibular body length on the affected side. These findings demonstrate the complex craniofacial morphology associated with unilateral coronal synostosis and highlight the role of the coronal suture in maintaining facial symmetry and the mandible's adaptive growth in response to glenoid fossa asymmetry.